2015
DOI: 10.1097/ede.0000000000000266
|View full text |Cite
|
Sign up to set email alerts
|

Mortality After the Death of a Spouse in Norway

Abstract: A considerable excess mortality risk was observed in widowed men and women from immediately after the loss of a spouse and for the next 10 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…After the first year of widowhood, excess mortality in our analysis stabilized over the subsequent 5 to 6 years, but remained high, which illustrates the long-term effect of widowhood. Indeed, other studies have shown that the risk of all-cause death remains elevated for at least 10 years after widowhood (Ytterstad and Brenn, 2015;Boyle et al, 2011). We found a long-term excess risk for each cause-group considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…After the first year of widowhood, excess mortality in our analysis stabilized over the subsequent 5 to 6 years, but remained high, which illustrates the long-term effect of widowhood. Indeed, other studies have shown that the risk of all-cause death remains elevated for at least 10 years after widowhood (Ytterstad and Brenn, 2015;Boyle et al, 2011). We found a long-term excess risk for each cause-group considered.…”
Section: Discussionmentioning
confidence: 99%
“…All information in Statistics Norway is updated annually. These data are not available to the public, and a detailed description of the material has been given elsewhere (Ytterstad and Brenn, 2015). Briefly, a total of 1,801,456 individuals who were registered as married in Statistics Norway in 1975 were followed for 32 years (from 1 January 1975 to 31 December 2006) for marital status and death, and widowed individuals were followed for mortality for 7 years following widowhood.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…An actuarial country wide Norwegian study of married couples reported similar risks but especially occurring in the first seven days[19] and in the younger-old. A particularly high risk occurred on the same day but that may simply be that both members of a couple dies in the same incident.…”
Section: Discussionmentioning
confidence: 99%